Identification of Smart Environment Readiness in Realizing Smart City Kotamobagu - Nini, Wa; Anripa, Nuralfin; Alian, La Ode; Maulana, Muh Vikky (Malikussaleh University, Aceh, Indonesia, 2024)
This study aims to identify the readiness of the innovative environment in realizing an intelligent city. A descriptive qualitative approach combined data collection techniques such as in-depth interviews, observation, and documentation. Primary data were obtained directly in the field through observation and interviews with diverse respondents. Secondary data were obtained from the Kotamobagu Environmental Service and the Kotamobagu PUPR Service. Data analysis was conducted through four stages: data collection, data reduction, data display, and conclusion drawing. The study results revealed that five innovative environment indicators were adequately met: the feasibility of water channels, irrigation channels, green space planning, water and air quality, and waste management systems. One indicator, the use of environmentally friendly energy resources, was not met. The study recommends that the Kotamobagu government develop policies or programs to build renewable energy resources to support the intelligent environment and realize Kotamobagu's smart city vision.